Phenolic profile and antioxidant, anti-inflammatory activity of Annona senegalensis, Ipomoea batatas, Terminalia superba and Psidium guajava Linn extracts used in Benin - Winsou, Irène; Anago, Eugénie; Dah-Nouvlessounon, Durand; Aclinou, Eustache; Nounagnon, Martial; Roko, Gautier; BABA-MOUSSA, LAMINE (My University, 2022)
The purpose of this study is to quantify the polyphenolic content and evaluated anti-inflammatory and antioxidant activity of four plants extracts of Annona senegalensis , Ipomoea batatas , Terminalia superba and Psidium guajava. Phenolic and flavonoid contents were determined by Folin-Ciocalteu and aluminum trichloride methods, respectively with ethanolic extract. The antioxidant activity was accessed by DPPH and FRAP methods. The results of the analysis of this study indicate that the ethanol extracts of the test plants (A. senegalensis , I. batatas , P. guajava and T. superba ) are potential source of natural antioxidant and anti-inflammatory.
Keywords: Antioxidant; In Vivo Anti-Inflammatory; Polyphenolic; Ethanol Extracts